Blood cell parameters for screening and diagnosis of hereditary spherocytosis. Issue 4 (3rd April 2019) - Liao, Lin; Xu, Yuchan; Wei, Hongying; Qiu, Yuling; Chen, Wenqiang; Huang, Jian; Tao, Yifeng; Deng, Xuelian; Deng, Zengfu; Tao, Hui; Lin, Faquan
Abstract : Background: There is currently no single index for the diagnostic screening of hereditary spherocytosis (HS). However, hematology analyzers are widely used in hospital laboratories because of their highly automated performance and quality control procedure, and detection of some blood cell parameters may be useful for the early screening of HS. Methods: We investigated the values of blood cell parameters for the screening and differential diagnosis of HS. We performed a descriptive study of 482 samples (67 cases of HS, 59 cases of G6PD deficiency, 57 cases of AIHA, 199 cases of thalassemia, and 100 cases of healthy controls) that were run on Beckman Coulter LH780 Hematology Analyzer. Results: HS was characterized by increased MCHC, decreased MRV, MSCV‐MCV < 0, and increased Ret with no concomitant increase in IRF. The areas under the ROC curves were MSCV‐MCV (0.97; 95% CI 0.95‐1.0) > MRV (0.94; 95% CI 0.91‐0.97) > MCHC (0.92; 95% CI 0.88‐0.97) > Ret/IRF (0.77; 95% CI 0.7‐0.84). MSCV‐MCV ≤ 0.6 fl was valuable parameter for the diagnostic screening of HS, with a sensitivity of 95.5% and specificity of 94.9%. Conclusion: These indices have high reference values for differentiating HS from thalassemia, AIHA, and G6PD deficiency.